A Numerical Approach for Fredholm Delay Integro Differential Equation - Cimen, Erkan; Enterili, Kubra (Communications in Mathematics and Applications, 2021)
This paper deal with the initial-value problem for a linear first order Fredholm delay integro differential equation. To solve this problem numerically, a finite difference scheme is presented, which based on the method of integral identities with the use of exponential form basis function. As a result of the error analysis, it is proved that the method is first-order convergent in the discrete maximum norm. Finally, an example is provided that supports the theoretical results.
Keywords: Fredholm delay integro differential equation; Finite difference method; Error estimate